2017
DOI: 10.1038/nature21368
|View full text |Cite
|
Sign up to set email alerts
|

Complement drives glucosylceramide accumulation and tissue inflammation in Gaucher disease

Abstract: Gaucher disease is caused by mutations in GBA1, which encodes the lysosomal enzyme glucocerebrosidase (GCase). GBA1 mutations drive extensive accumulation of glucosylceramide (GC) in multiple innate and adaptive immune cells in the spleen, liver, lung and bone marrow, often leading to chronic inflammation. The mechanisms that connect excess GC to tissue inflammation remain unknown. Here we show that activation of complement C5a and C5a receptor 1 (C5aR1) controls GC accumulation and the inflammatory response i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
143
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(173 citation statements)
references
References 25 publications
10
143
0
1
Order By: Relevance
“…Previous studies have shown that these glycosphingolipids modulate β-cell immune receptor signaling (Boslem et al, 2012;Osterbye et al, 2010) as well as aggravate systemic inflammation responses (Mobarak et al, 2018;Pandey et al, 2017). Elevated glycoceramide levels in PBMCs in autoantibody-positive children who later progress to T1D, as observed in our study, therefore point to a specific sphingolipid pathway in immune cells which contributes to T1D pathogenesis.…”
Section: Discussionsupporting
confidence: 74%
“…Previous studies have shown that these glycosphingolipids modulate β-cell immune receptor signaling (Boslem et al, 2012;Osterbye et al, 2010) as well as aggravate systemic inflammation responses (Mobarak et al, 2018;Pandey et al, 2017). Elevated glycoceramide levels in PBMCs in autoantibody-positive children who later progress to T1D, as observed in our study, therefore point to a specific sphingolipid pathway in immune cells which contributes to T1D pathogenesis.…”
Section: Discussionsupporting
confidence: 74%
“…In patients with Gaucher disease, who are susceptible to developing myeloma 25 , clonal immunoglobulin was reactive against lyso-glucosylceramide (an acyl group derivative of glucosylceramide) owing to a deficiency in glucocerebrosidase/glucosylceramidase, which is highly elevated in these patients 140 . Interestingly, in Gaucher disease, complement signalling via complement C5a and C5a receptor 1 (C5aR1) induced the accumulation of glucosylceramide and tissue inflammation 141 . Moreover, CERS6-generated C16 ceramide increased T cell response to alloantigens during allogeneic haematopoietic stem cell transplantation (allo-HSCT) in a mouse model of leukaemia, an effective immunotherapy for various haematological malignancies 142 .…”
Section: Sphingolipids and Cancer Therapymentioning
confidence: 99%
“…Although the connection of complement with another chronic bone loss disorder, periodontitis, was earlier suggested by correlative clinical studies, new interventional studies in non-human primates demonstrated a causative link between C3 activation and inflammatory periodontal bone loss 82,83 . Furthermore, complement was recently incriminated in Gaucher disease (GD), a genetically driven lysosomal storage disorder associated with dysregulated glycolipid metabolism in various tissues 84 . GD is associated with chronic inflammation marked by a pronounced autoimmune response to intracellularly accumulated glucosylceramide.…”
Section: Complement In Inflammatory Diseasesmentioning
confidence: 99%
“…GD is associated with chronic inflammation marked by a pronounced autoimmune response to intracellularly accumulated glucosylceramide. Robust clinical evidence and data from animal studies implicated C5a-C5aR1 signaling in a vicious cycle that fuels chronic inflammation in GD through C5aR1-driven glycolipid accumulation and modulation of glucosylceramide-specific autoantibody generation 84 . Finally, the kidneys are particularly susceptible to damage induced by complement-mediated inflammation, which appears to drive various renal disorders (reviewed in refs.…”
Section: Complement In Inflammatory Diseasesmentioning
confidence: 99%